2004
DOI: 10.1002/pd.866
|View full text |Cite
|
Sign up to set email alerts
|

Fetal serum ß2‐microglobulin and cystatin C in the prediction of post‐natal renal function in bilateral hypoplasia and hyperechogenic enlarged kidneys

Abstract: In bilateral renal hypoplasia and dysplasia, fetal serum ss2-microglobulin and cystatin C are good markers for post-natal renal function. However, in bilateral renal hyperechogenic enlargement, abnormal values are associated with poor post-natal renal function, but normal values cannot preclude renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
3
40
0
1
Order By: Relevance
“…Besides reporting for the first time the presence of a high prevalence of TCF2 gene anomalies in antenatal hyperechogenic kidneys, we confirm the typical in utero presentation of ARPKD with enlarged hyperechogenic kidneys Ͼ2 SD with loss of corticomedullary differentiation, presumably as a result of the numerous small cysts that are undetectable by ultrasound and the constant decrease in amniotic fluid volume (1,2,21). These characteristics resulted in TOP in 10 of 12 cases and one neonatal death in our cohort.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Besides reporting for the first time the presence of a high prevalence of TCF2 gene anomalies in antenatal hyperechogenic kidneys, we confirm the typical in utero presentation of ARPKD with enlarged hyperechogenic kidneys Ͼ2 SD with loss of corticomedullary differentiation, presumably as a result of the numerous small cysts that are undetectable by ultrasound and the constant decrease in amniotic fluid volume (1,2,21). These characteristics resulted in TOP in 10 of 12 cases and one neonatal death in our cohort.…”
Section: Discussionsupporting
confidence: 60%
“…Several data showed that enlargement of the kidneys Ͼ2 SD and severe oligohydramnios are predictive markers of poor renal function (1,2). However, the postnatal prognosis of renal dysplasia with normal amniotic fluid is very difficult to predict (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations